2016
DOI: 10.1177/1757913916630009
|View full text |Cite
|
Sign up to set email alerts
|

Sheffield Hallam Staff Wellness service: Four-year follow-up of the impact on health indicators

Abstract: Aims: Alongside the increasing prevalence of chronic health conditions such as cardiovascular disease and diabetes, has been an increase in interventions to reverse these ill-health trends. The aim of this study was to examine the longitudinal impact of the Sheffield Hallam University Staff Wellness Service on health indicators over a five year period. Methods:The Sheffield Hallam Staff Wellness Service was advertised to university employees. Of 2561 employees who have attended the service, 427 respondents (ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Research also suggested that workplaces supporting PA, health and wellbeing programmes observed benefit in various ways, including improved productivity, higher staff retention, greater loyalty, and reduced sickness absences [ 16 ]. However, there is a mixture of findings without clear guidelines to understand which interventions were most suitable to be effective in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…Research also suggested that workplaces supporting PA, health and wellbeing programmes observed benefit in various ways, including improved productivity, higher staff retention, greater loyalty, and reduced sickness absences [ 16 ]. However, there is a mixture of findings without clear guidelines to understand which interventions were most suitable to be effective in this environment.…”
Section: Introductionmentioning
confidence: 99%
“…The National Institute for Health and Care Excellence (NICE) has published several evidence-based guidelines for employers on how to improve the health of staff (management of long-term sickness absence, mental wellbeing, obesity, smoking cessation and physical activity in the workplace) [ 19 – 24 ]. Data from controlled and uncontrolled studies has revealed workplace HWB services can maintain good health status among employees over the long-term [ 25 ] and deliver significant changes in alcohol consumption, nutrition, sleep, stress, body mass index, depression and perceptions of general health [ 26 28 ], including some long-term improvements in body mass, waist circumference, blood pressure and lipid profiles compared to controls [ 29 ]. Several studies have also reported positive outcomes of workplace HWB services delivered in the NHS, including long-term changes to physical activity (in and out of work), significantly lower sickness absence, greater job satisfaction and greater organisational commitment [ 30 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…Commentators on workplace health and sedentary behaviour [1,[12][13][29][30][31] advocate that the workplace can lead to sustainable change, as organisational practice, policy, established communication channels, in-built social support from colleagues and management systems can all encourage healthy behaviour change. Our study identified that endorsement from the organisation was the key mediator in workplace behaviour change.…”
Section: Discussionmentioning
confidence: 99%